(untitled) (Al-Qamar, 2023)
Maqbool Aamir, a Legendary Poet got birth during 1954 in the fertile land of Bannu; one of the beautiful cities of southern belt of Khyber Pakhtunkhwa. The land of Bannu is also fertile in the field of literature. This land owns a number of literati and Maqbool Aamir is one amongst them. His original name was Syed Maqbool Hussain Shah while he is known as Maqbool Aamir amongst poets. His forefathers link to Hazrat Bahaud Din Zakariya Multani. He got his early education at Bannu, and got the degree of M.A. Urdu from University of Peshawar. He joined Academy Adabiyat Islamabad as Research Officer in 1984. He got the fatal disease of Scleroderma at the very young age. He tried his best to get sound health. He went to London for treatment but could not fight against the disease. At last left the legacy and friends in tears on May 31st, 1991. May his soul rest in peace. During 1990, one year before his death, he published his book “Diyay Kī Ānkh” ,”. The book consists of 52 Ghazals, 25 poems, 6 couplets and a number of songs. Maqbool Aamir was an innovative poet and very soon he became a reference. His poetry has got a vivid picture of real and deeper feelings. His personal life is reflected in his poetry, but he is always an optimistic. “Hum Ahele Shab K Liyay Subh Ka Hawalaa Hay… Diyay Kī Ānkh Men Aansoo Nahi, Ujala Hay.” He had always been in the search of such an honest leader, who could lead him towards light. He was a humanist poet with a healing heart in his chest. Most of his poems even show love for animals and birds. His poetry has got aphoristic style with simple approach towards life. He is considered to be the painter of life. He expressed what he felt. He touched every corner of life; if it is romance or social problem.